Hegemoni Ideologi Konsumtif Sebagai Gaya Hidup Remaja - Yofiendi Indah Indainanto (JURNAL SIMBOLIKA: Research and Learning in Communication Study (E-Journal), 2020)
The new media provides a powerful influence in shaping the knowledge and character of adolescents as a middle class group. Content packaging is represented as naturally as possible in capturing its influence, so that a hegemony practice takes place. Content that emphasizes and accentuates consumptive culture is used as a mainstay to attract the attention of audiens through Youtube channel to increase the number of viewrs to gain profit. This practice is what makes consumptive hegemony make audines subject to approval. This study describes how the practice of hegemony in shaping consumptive ideology, uses qualitative studies with a literary approach to strengthen Gramsci's hegemony explanations. Ria Ricis official Youtube channel analysis object with colorful and squsihy shopping content themes. The results show that the account packages content by cultivating the effect of pleasure in emphasizing consumptive ideology and uploading similar content with the same theme because of the approval. Social media provides a closeness between audiens and content owners so that the practice of hegemony is easily subjected to approval. In defending consumptive ideology, the dominant group makes representations that allow good responses. the hegemony made the consumptive ideology develop into a lifestyle.